Síndrome de Guillain - Barre - Strohl en niños: características clínicas y de líquido cefalorraquídeo - Recuenco Cabrera, Sergio Eli (1992)
We checked twenty-nine clinical histories of children with Guillain-Barré-Strohl Syndrome from eleven months to fourteen years of age, interned in the Bethlehem Support Hospital of Trujillo, from January 1980 to December 1991, were reviewed in order to determine the characteristics clinical and cerebrospinal fluid. The results were: 1. The average age of the series of 7.9 years, and the age group of 5 to 9 years was the most affected. 2. There was a predominance of males with an index of 1.4 to 1. 3. There were non-neurological concomitant symptoms in 75.9%, and the most frequent were sensation of thermal rise, cough, headache and diarrhea. 4. Pathological history was found in 34.4%, the most frequent being acute respiratory infection. 5. Neurological symptoms appeared on average 2.7 days after the onset of the disease. 6. The installation time of the complete neurological clinical picture was 9.2 days on average, being one week for 75% of patients. 7. The motor commitment was presented in 100% and the mode of extension of the motor deficit was the increase in 93%. 8. Paresthesias were reported in 62% of the cases. 9. In the period of state, the following neurological signs were found in order of frequency: a) Motor deficit of the four extremities in 89.6%; b) Areflexia and hyporeflexia in 82.7%; c) Muscle hypotonia in 65.5%; d) Commitment of cranial pairs in 41%; e) Commitment of respiratory muscles in 24%; f) Sensitive commitment in 20.7%; g) Sphincter commitment in 13.8%; h) Meningeal signs in 10.3% 10. Complications occurred in 17.2%, with bronchopneumonia and urinary tract infection being more frequent. 11. The hospital stay was on average two weeks and 79.3% of patients came out in improved condition. 12. In the cerebrospinal fluid: a) Albumin-cytological dissociation was found in 75% of the samples. b) The proteinorráquia average was 0.967 g / L. c) The average glucurrachia was 0.456 g / L. d) An average of 4.3 leukocyte / mm³ was found. 13. There was a 10.3% lethality. It is concluded that some characteristics of neurological involvement; motor deficit with acute onset, symmetrical, ascending and distal, areflexia and / or hyporeflexia, with albúmico-cytological dissociation of cerebrospinal fluid and with reversibility of paralysis; they are diagnostic elements for our environment